The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7567/jjap.54.07hc16
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave mapping of skeletal muscle using shear wave wavefront reconstruction based on ultrasound color flow imaging

Abstract: We have proposed a quantitative shear wave imaging technique for continuous shear wave excitation. Shear wave wavefront is observed directly by color flow imaging using a general-purpose ultrasonic imaging system. In this study, the proposed method is applied to experiments in vivo, and shear wave maps, namely, the shear wave phase map, which shows the shear wave propagation inside the medium, and the shear wave velocity map, are observed for the skeletal muscle in the shoulder. To excite the shear wave inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Powdered agar (g) Sterilized milk (ml) www.nature.com/scientificreports/ showed that shear wave velocity measurements in phantom gels, supraclavicular muscles, and trapezius muscles acquired using the new method were consistent with those acquired by means of other instruments 15,33,34,51,52 .…”
Section: Concentration (%)mentioning
confidence: 70%
See 1 more Smart Citation
“…Powdered agar (g) Sterilized milk (ml) www.nature.com/scientificreports/ showed that shear wave velocity measurements in phantom gels, supraclavicular muscles, and trapezius muscles acquired using the new method were consistent with those acquired by means of other instruments 15,33,34,51,52 .…”
Section: Concentration (%)mentioning
confidence: 70%
“…3), tissues can be readily measured close to the body surface; however, the measurement of deep tissues may be difficult. A previous study 51 showed that stable measurement of deeper tissues may be achieved by modifying the shear wave frequency of the actuator with respect to shear wave tissue absorption. However, the feasibility of this approach must be confirmed through additional investigations.…”
Section: Concentration (%)mentioning
confidence: 99%
“…Several methods have been proposed as SWI and they have been applied to various tissues, for example, breast, liver and thyroid gland, in which the hardness of the tissue is sensitive to diseases. We have proposed a novel SWI method (Color Doppler SWI: CD SWI) for continuous shear wave which is excited by a mechanical vibrator [1,2]. In this method, shear wave propagation inside the tissue is appeared directly on the color flow map of conventional ultrasound imaging system without adding any extra function to the imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Several methods for SWEI have been proposed, including strain elastography and ultrasound push pulse-based shear wave elastography. [5][6][7][8][9][10][11] Strain elastography has a number of advantages over other elastography methods, including quick and easy image acquisition. However, because quantification using this method is difficult, relative evaluations, such as the Tsukuba-score for thyroid nodules, are generally employed.…”
Section: Introductionmentioning
confidence: 99%
“…CFIs including the shear wave wavefront can contain various artifacts from standing waves or reflected waves at tissue boundaries. To suppress the phase variations on shear wave phase maps, the current Fourier analysis requires at least 32 CFI frames to be captured every 2 to 3 s. 11 The phase amount on the phase map is calculated by applying fast Fourier transform (FFT) to the time axis that is the frame direction for each pixel. However, maintaining real-time CD SWI is clinically important; real-time visualization of shear wave propagation on shear wave phase and velocity maps is required to allow physicians to properly position the vibrator and receiver device for image acquisition.…”
Section: Introductionmentioning
confidence: 99%